COPAIBA OIL INFLUENCES VENTRAL HERNIA REPAIR WITH VICRYL® MESH? - YASOJIMA,Edson Yuzur (2015)
Background: The use of meshes in hernia surgical repair promoted revolution in the surgical area; however, some difficulties had come, such as a large area of fibrosis, greater postoperative pain and risk of infection. The search for new substances that minimize these effects should be encouraged. Medicinal plants stand out due possible active ingredients that can act on these problems. Aim: To check the copaiba oil influence in the repair of abdominal defects in rats corrected with Vicryl(c) mesh. Method: Twenty-four Wistar rats were submitted to an abdominal defect and corrected with Vicryl(c) mesh. They were distributed into two groups: control and copaíba via gavage, administered for seven days after surgery. The analysis of the animals took place on 8, 15 and 22 postoperative days. It analyzed the amount of adhesions and microscopic analysis of the mesh. Results: There was no statistical difference regarding the amount of adhesions. All animals had signs of acute inflammation. In the control group, there were fewer macrophages in animals of the 8th compared to other days and greater amount of necrosis on day 8 than on day 22. In the copaiba group, the number of gigantocytes increased compared to the days analyzed. Conclusion: Copaiba oil showed an improvement in the inflammatory response accelerating its beginning; however, did not affect the amount of abdominal adhesions or collagen fibers.